2021
DOI: 10.3390/ani11092672
|View full text |Cite
|
Sign up to set email alerts
|

Birth Weight and Nutrient Restriction Affect Jejunal Enzyme Activity and Gene Markers for Nutrient Transport and Intestinal Function in Piglets

Abstract: Significant variation in the birth weight of piglets has arisen due to increased sow prolificacy. Intestinal development and function may be affected by birth weight. Low birth weight (LBW) pigs may also have reduced feed intake, leading to further impairment of intestinal development. The objective of this study was to examine the intestinal development pattern of LBW and normal birth weight (NBW) piglets with normal nutrition (NN) or restricted nutrition (RN) in the pre-weaning period. Jejunal intestinal sam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Peptides and amino acids are the final by-products of protein digestion, which are subsequently absorbed by amino acid transport carriers in the intestine. For instance, SLC1A1 in the gut absorbs glutamate and aspartate, while PepT1 transports dipeptides and tripeptides ( Spanier and Rohm, 2018 ; Wellington et al., 2021 ). Interestingly, we also detected higher levels of nutrient transporters at the gene and protein levels in the jejunal and ileal mucosa of EO-fed pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Peptides and amino acids are the final by-products of protein digestion, which are subsequently absorbed by amino acid transport carriers in the intestine. For instance, SLC1A1 in the gut absorbs glutamate and aspartate, while PepT1 transports dipeptides and tripeptides ( Spanier and Rohm, 2018 ; Wellington et al., 2021 ). Interestingly, we also detected higher levels of nutrient transporters at the gene and protein levels in the jejunal and ileal mucosa of EO-fed pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Nutrient uptake is not only the first step for nutrient absorption, but also the main source of energy and nutrients for intestinal metabolism and development. Accumulating evidence showed that intestinal growth stagnation and dysfunction in piglets with IUGR are accompanied by a series of nutrient transporter changes and disorders of nutrient and energy metabolism [30][31][32]. It has been reported that mRNA expression of several nutrient transporters including SLC1A1, SLC7A7, SLC7A9, PepT1, FABP4, SLC5A1, and GLUT2 was significantly reduced in the jejunum of IUGR piglets [30], implying that inadequate nutrient uptake is strongly associated with impaired gut development and function.…”
Section: Discussionmentioning
confidence: 99%